PEMANFAATAN MEDIA SOSIAL DALAM MENINGKATKAN LITERASI KEMAMPUAN BAHASA INGGRIS KEPADA REMAJA - Harahap, Olivia Feby; Nasution, Nurul Hidayah (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
Abstract Millennials need English because the boundaries between countries are no longer visible. This makes us have to be able to communicate using international languages, and English is one of them. However, the impact of implementing the 2013 curriculum on reducing the number of hours for several subjects including English subjects reduced the effort to learn the language. Need a strategy to facilitate mastery of the language. Focusing on language skills such as speaking, writing, listening and reading is one way. Seeing the complex problem of mastering the language, students of SMPN 1 Angkola Barat need help to master English. This assistance is only temporary because after that students are expected to be able to independently make efforts to improve their language skills. These things are the focus of community service carried out by FIB Unsoed lecturers. Formal classes that cannot provide writing competence training are the main background for this service. Thus, the purpose of this service is to improve writing skills through English literacy activities. The methods used are lectures, posters and workshops. The result of this service is a collection of short story books with 18 stories in it, which is proof of the success of this service. Keywords: writing, reading, literacy, book level